Preliminary study of blood pressure and arterial stiffness monitoring using the niva device (non-invasive vascular analyzer) - Reformia Avianningsih; Patonah Hasimun; Garnadi Jafar; Al-fira Putriyanti; Hasballah Zakaria (Science Midwifery, 2026)
Introduction: Measuring vascular parameters using the NIVA (Non-Invasive Vascular Analyzer) is an important step in assessing the health of blood vessels in the community, especially in groups at risk of hypertension. Objective: This study aims to describe the results of baseline blood pressure and vascular parameter examinations in respondents before further intervention. Methods: Respondents underwent an initial screening process including informed consent, anamnesis, and baseline blood pressure measurement. Results: The graph shows a balanced gender distribution and a dominance of the 31-40 and 41-50 age groups, which are age groups at high risk of experiencing increased arterial stiffness. The hand and foot blood pressure graphs show variations in systolic and diastolic values ​​​​in the mild to moderate hypertension range, indicating that the hemodynamic condition of the respondents is stable and safe for NIVA examination. NIVA measurements were performed by attaching a cuff to the upper arm and left ankle to obtain parameters such as baPWV, ABI, MAP, PP, and Vascular Age. Blood pressure variations in the baseline graph support accurate reading of vascular parameters, especially because there was no indication of peripheral stenosis based on the comparison of hand and foot blood pressure. The data recording and validation process was performed by comparing the measurement results to the baseline, which was consistent with the initial graph. Conclusion: The examination results indicate that the respondents' initial condition met the requirements for non-invasive vascular evaluation and provided a representative picture of blood vessel health status prior to clinical intervention.